Death With Tuberculosis in California, 1994–2008. (1st October 2014) - Pascopella, Lisa; Barry, Pennan M.; Flood, Jennifer; DeRiemer, Kathryn
Abstract: Background.  Identifying factors associated with tuberculosis (TB) deaths will inform efforts to prevent deaths. Methods.  We examined deaths among patients with culture-confirmed TB reported to the California TB Registry during 1994–2008. We calculated the age-adjusted percentage of deaths before and during TB treatment and estimated trends. We constructed multivariable logistic regression models to identify factors associated with death during treatment. Results.  Of 40 125 patients with culture-confirmed TB, 4565 (11%) died: 1146 (25%) died before treatment started, and 3419 (75%) died during treatment. The age-adjusted percentage of patients who died before and during treatment declined from 1994 to 2008 (3.5% to 2%, and 10.4% to 7.2%, respectively, both P < .0001). We identified several risk factors for death that may be addressed with public health efforts: acquired multidrug resistance (adjusted odds ratio [aOR] = 4.67; 95% confidence interval [CI], 2.09–10.45); care in the private sector (aOR = 3.08; 95% CI, 2.75–3.44); and an initial treatment regimen of <3 drugs (aOR = 2.07; 95% CI, 1.63–2.64). We identified other risk factors for death that could be used as markers for intensified diagnostic and treatment processes in hospital: human immunodeficiency virus coinfection; meningeal, peritoneal, and disseminated TB; substance use; and abnormal chest radiograph without cavities. Conclusions.  In California, 1 in 9 TB patients died with a potentially curable disease. Public health departments might prevent deaths in patients with TB by strengthening partnerships with private providers, intensifying diagnostic and treatment processes for patients at risk of death in hospital, optimizing treatment regimens for patients with comorbidities, and preventing the acquisition of drug resistance.